Kajian Strategi Pengembangan Rantai Nilai Agribisnis Kelapa Meningkatkan Nilai Tambah dan Kemandirian Pangan di Bireuen - Desparita, Naya; Elfira; Muhammad Baidhawi; Syahirman Hakim (JURNAL AGRICA, 2025)
This study discusses the potential and strategies for coconut agribusiness development in Bireuen Regency, supported by agroclimatological conditions, land use, and traditional cultivation traditions. There are four main sub-districts that are production centers with abundant coconut populations: Peusangan, Juli, Jeumpa, and Simpang Mamplam. The results show that coconut agribusiness development involves aspects of production, processing, marketing, infrastructure, human resources, technology and innovation, and policy. Through AHP analysis, the production aspect has the highest weight (27.4%), while the human resources aspect has the lowest weight (1.78%). The main actors involved are farmers (weight 0.503), followed by the processing industry (0.201), collecting agents (0.195), and government institutions (0.101). The prioritized strategic objectives are increasing added value (0.453), increasing farmer income (0.364), and food independence (0.183). The results of this study have very important implications for policy making in coconut agribusiness practices in Bireuen Regency, this is indicated by the research findings that human resources have a low weight so that increasing the capacity of farmer skills needs to be done through workshops on diversification of derivative products to innovate to meet market needs. The main roles in the coconut value chain are farmers and processing industries, a strategy is needed in developing the coconut value chain in a sustainable manner so that it can increase added value and farmer welfare in supporting food independence in Bireuen Regency.